Electrochromic Properties of Rf-Sputtered wo3 Films: An Impact of Post-Annealing and Room Temperatures for Smart Window Applications - Radhalayam, D (Springer, 2024)
Tungsten oxide (WO3) thin films were deposited on glass substrates of Corning glass (CG) and fluorine-doped tin oxide (FTO) using an RF magnetron sputtering process. The effects of varying the annealing temperature on structural, surface morphology, optical properties, and electrochromic (EC) are examined using X-ray diffraction, Fourier-transform infrared spectroscopy (FTIR), SEM, Raman spectroscopy, UV-Vis spectroscopy, and cyclic voltammetry. WO3 thin films annealed at 573 K and 673 K were shown by SEM analysis to have fewer cracks after being found to crack more at 773 K. According to the XRD investigation, the WO3 thin films annealed at 573 K, 673 K, and 773 K had a crystalline nature. At 773 K, when the coloring efficiency (CE) was determined to be 40.45 cm2/s, the diffusion coefficient was found to be the lowest (1.7 × 10−14 cm2/C). At 573 K, the coloring efficiency (CE) was measured to be 52.38 cm2/C, and at 673 K, it was 39.33 cm2/C. It has been discovered that post-annealing significantly affects color efficiency, which is important in electrochromic (EC) applications. © The Author(s) under exclusive licence to Sociedade Brasileira de Física 2024.